Aluminum alloy sheet and method for manufacturing an aluminum alloy sheet
Patent Information
- Application Number
- JP2025059109
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166265000010 
Figure 2026166265000011 
Figure 2026166265000001
Abstract
Description
[Technical Field]
[0001] This invention relates to an aluminum alloy sheet and a method for manufacturing an aluminum alloy sheet. [Background technology]
[0002] In recent years, due to concerns about the global environment, there has been an increasing social demand for lighter automobile bodies. To meet this demand, aluminum alloy materials are being applied to parts of automobile bodies, such as panels (outer panels such as hoods, doors, and roofs, and inner panels), bumper reinforcements (bumper R / F), and door beams, replacing the steel materials used previously.
[0003] On the other hand, since automobiles also require a certain design aesthetic in terms of shape, in addition to the weight reduction and rigidity necessary for automotive applications, processability is also important.
[0004] For example, in automotive applications such as hoods and doors, the outer and inner panels are press-formed separately, and then the outer panel is hemmed (bent) by 180° and fastened to the inner panel.
[0005] During the bending process described above, high strain is concentrated locally at the bending ridge, making it prone to cracking. Therefore, the outer panel requires high bendability.
[0006] Furthermore, since the outer panel is a part that consumers see, it is necessary to ensure a good appearance. In contrast, if the panel material deforms, slight irregularities may occur on the surface, resulting in a poor appearance, so good surface properties are required after press molding.
[0007] In contrast, Patent Document 1 discloses that by setting an appropriate cooling rate after homogenization heat treatment, holding the ingot after homogenization heat treatment within a certain temperature range before the start of hot rolling, and setting the cold rolling ratio in cold rolling to 65% or more, an aluminum alloy sheet with excellent bendability and surface quality can be obtained. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Japanese Patent Publication No. 2018-16879 [Overview of the project] [Problems that the invention aims to solve]
[0009] In the invention described in Patent Document 1, after homogenization heat treatment, the material is cooled, and then, before the start of hot rolling, a heat treatment is performed in which the material is held within a certain temperature range.
[0010] In response to this, the inventors investigated and found that, as described above, there is a concern that performing cooling or heat treatment that involves holding the material within a certain temperature range between the homogenization heat treatment and hot rolling may coarseen the Mg-Si compounds. More specifically, as described in Patent Document 1, if cooling is performed after the homogenization heat treatment, and then heat treatment that involves holding the material within a certain temperature range before the start of hot rolling is performed, coarse Mg-Si compounds precipitate during the cooling process, resulting in limited improvement in bendability. Furthermore, the process of cooling after the homogenization heat treatment and holding the material within a certain temperature range before the start of hot rolling requires time for cooling and additional heat treatment, resulting in poor productivity.
[0011] Regarding bendability, there has been a growing demand for improved bendability of 6000 series aluminum alloy sheets, particularly in recent years. This is due to the increasing need for sharper character lines in automobiles and other applications, as well as the need to ensure greater flexibility in combining the thicknesses of outer and inner panels during bending processes by automobile manufacturers. It is difficult for the aluminum alloy sheet disclosed in the above Patent Document 1 to cope with the formability in such severe bending processing with further increasing requirements.
[0012] Accordingly, the present invention aims to provide an aluminum alloy sheet that achieves both excellent bendability and surface quality, which can meet the strict requirements for bending processing as described above and the requirement of good surface properties after press forming, and a method for producing the same. Furthermore, regarding the production method, another object is to provide a method for producing an aluminum alloy sheet that is excellent in productivity in addition to the above bendability and surface quality. [Means for Solving the Problems]
[0013] To solve the above problems, the present inventors conducted intensive studies, and as a result, found that the above problems can be solved by setting the aluminum alloy sheet to a specific composition range and performing the hot rolling step and the cold rolling step under specific conditions, without performing cooling or additional heat treatment between the homogenization heat treatment and the hot rolling, thereby completing the present invention.
[0014] That is, the gist of the present invention is as follows. [1] Si: 0.3 to 1.5 mass%, Fe: 0.15 to 0.4 mass%, Cu: 0.001 to 0.2 mass%, Mn: 0.02 to 0.3 mass%, Mg: 0.3 to 0.8 mass%, Cr: 0.001 to 0.3 mass%, Zn: 0.001 to 0.3 mass%, and Ti: 0.001 to 0.3 mass%, The aluminum alloy sheet with the balance consisting of Al and impurities, wherein the aluminum alloy sheet has a Cube orientation area ratio of 17 to 50%, and the number density of Mg-Si based compounds having an equivalent circle diameter of 0.4 μm or more in the aluminum alloy sheet is 2650 pieces / mm 2 or less. The number density of Al-Fe-Si compounds with an equivalent circular diameter of 2.0 μm or more in the aforementioned aluminum alloy plate is 225 to 700 particles / mm². 2 The following is an aluminum alloy plate. [2] The aluminum alloy sheet described in [1] above, used in automobiles.
[0015] [3] A casting process in which raw materials are melted and the molten metal, adjusted to a predetermined chemical composition, is cast into an ingot. A homogenization heat treatment step in which the cast ingot is subjected to a homogenization heat treatment, A hot rough rolling process in which a homogenized ingot is hot rough rolled to obtain a hot rough rolled plate. A hot finishing rolling process to obtain a hot finishing rolled sheet by hot finishing rolling the aforementioned hot rough rolled sheet, A cold rolling process to obtain a cold-rolled sheet by cold-rolling the hot-finished rolled sheet, and A method for manufacturing an aluminum alloy sheet, comprising, in sequence, a solution treatment step of solution treatment of the cold-rolled sheet, The homogenization heat treatment step is performed in a temperature range of 520 to 580°C. Without performing cooling and additional heat treatment between the homogenization heat treatment step and the hot rough rolling step, The hot roughing process described above involves a final pass where the Z factor, as shown by the following formula, is 1.0 × 10⁻⁶. 8 ~5.0×10 11 Perform the procedure under the following conditions:
[0016]
number
[0017] (In the above equation, ε' represents the strain rate, Q represents the activation energy, R represents the gas constant, and T represents the temperature.) The aforementioned hot finishing rolling process is completed at a temperature of 250°C or higher and less than 350°C. The cold rolling process is carried out so that the cold rolling ratio is 74-95%. The resulting aluminum alloy sheet is Si: 0.3~1.5% by mass, Fe:0.15~0.4% by mass, Cu:0.001~0.2% by mass, Mn: 0.02~0.3% by mass, Mg: 0.3~0.8% by mass, Cr:0.001~0.3% by mass, Zn: 0.001~0.3 mass%, and Ti: satisfies 0.001~0.3 mass%, A method for manufacturing an aluminum alloy sheet, wherein the remainder consists of Al and impurities.
[0018] [4] A method for manufacturing an aluminum alloy sheet according to [3], wherein the homogenization heat treatment step is performed for 1 to 30 hours. [5] The method for manufacturing an aluminum alloy sheet according to [3] or [4], wherein the hot rough rolling step is performed with an entry temperature of 400 to 570°C. [6] A method for manufacturing an aluminum alloy sheet according to any one of [3] to [5], comprising a step of performing intermediate annealing before or during the cold rolling step. [7] The method for manufacturing an aluminum alloy sheet according to [6], wherein the intermediate annealing is performed at a temperature range of 300 to 450°C for 1 to 20 hours. [8] The method for manufacturing an aluminum alloy plate according to any one of [3] to [7], wherein the solution treatment step is performed in a temperature range of 520 to 580°C. [9] A method for manufacturing an aluminum alloy plate according to any one of [3] to [8], wherein after the solution treatment, the aluminum alloy plate is cooled at a cooling rate of 1 to 100°C / second.
[10] A method for manufacturing an aluminum alloy plate according to any one of [3] to [9], wherein within 10 minutes after the solution treatment step, the plate is held at a temperature range of 50 to 100°C for 1 to 50 hours for a preliminary aging treatment. [Effects of the Invention]
[0019] According to the present invention, an aluminum alloy sheet can be obtained that achieves both excellent bendability and surface quality, meeting stringent requirements for surface properties after bending and press forming. Furthermore, since such an aluminum alloy sheet can be obtained by homogenization heat treatment at a single temperature, the load on the heat homogenization equipment can be reduced, which is also preferable from the viewpoint of productivity. [Brief explanation of the drawing]
[0020] [Figure 1] Figure 1 is a schematic perspective view of the apparatus used in the VDA bending test to evaluate bendability. [Figure 2] Figure 2 is a diagram illustrating a punch, which is a bending jig used to apply a load to a test specimen from above in the apparatus shown in Figure 1. The left side of Figure 2 is a front view of the punch, and the right side of Figure 2 is a side view of the punch. [Modes for carrying out the invention]
[0021] The aluminum alloy plate according to this embodiment and embodiments for manufacturing the aluminum alloy plate will be described in detail below. Although the present invention has been described in detail and with reference to specific embodiments, it will be apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the invention. In this specification, the "~" symbol indicating a numerical range is used to mean that the numbers written before and after it are included as the lower and upper limits, respectively.
[0022] Method for manufacturing aluminum alloy sheets The method for manufacturing an aluminum alloy sheet according to this embodiment includes the following steps in order. Process 1: A casting process in which raw materials are melted and the molten metal, adjusted to a predetermined chemical composition, is cast into an ingot. Process 2: A homogenization heat treatment process in which the ingot cast in Process 1 is subjected to a homogenization heat treatment. Step 3: Hot rough rolling process to obtain a hot rough rolled plate by hot rough rolling the ingot homogenized in Step 2. Step 4: A hot finishing rolling process in which the hot rough-rolled sheet obtained in Step 3 is hot-finished to obtain a hot-finished rolled sheet. Step 5: A cold rolling process in which the hot-finished rolled sheet obtained in Step 4 is cold-rolled to obtain a cold-rolled sheet. Step 6: Solution treatment step in which the cold-rolled sheet obtained in Step 5 is subjected to solution treatment.
[0023] The process may further include an intermediate annealing step before the cold rolling step in step 5 described above, or during the cold rolling step. In step 6 described above, cooling may be performed at a predetermined cooling rate after the solution treatment. The solution treatment step in step 6 described above may further include a step of performing a preliminary aging treatment. Furthermore, no cooling or additional heat treatment is performed between the homogenization heat treatment step 2 and the hot rough rolling step 3.
[0024] In the manufacturing method of the aluminum alloy sheet according to this embodiment, in the homogenization heat treatment step 2, a homogenization heat treatment is performed in the temperature range of 520 to 580°C. Furthermore, in the hot rough rolling step 3, the final pass is performed when the Z factor shown in the following formula is 1.0 × 10⁻⁶ 8 ~5.0×10 11 The process will be carried out under the following conditions. Furthermore, the hot finishing rolling process in step 4 will have a final temperature of 250°C or higher and less than 350°C. Subsequently, the cold rolling process in step 5 will be carried out so that the cold rolling ratio is 74-95%.
[0025]
number
[0026] (In the above equation, ε' represents the strain rate, Q represents the activation energy, R represents the gas constant, and T represents the temperature.)
[0027] Furthermore, the resulting aluminum alloy sheet satisfies the following alloy composition. Si: 0.3~1.5% by mass, Fe:0.15~0.4% by mass, Cu:0.001~0.2% by mass, Mn: 0.02~0.3% by mass, Mg: 0.3~0.8% by mass, Cr:0.001~0.3% by mass, Zn: 0.001~0.3 mass%, and Ti: satisfies 0.001~0.3 mass%, The remainder consists of Al and impurities.
[0028] The details of each of the above processes and the resulting aluminum alloy sheet are described below.
[0029] <Process 1: Casting Process> Step 1 is a casting process in which raw materials are melted and the molten metal, adjusted to a predetermined chemical composition, is cast into an ingot.
[0030] The melting of the raw materials is adjusted so that the resulting aluminum alloy plate falls within the desired composition range. The method for casting the adjusted molten aluminum alloy into an ingot is not particularly limited, and conventionally known methods can be employed. Casting methods include, for example, continuous casting and semi-continuous casting (DC casting). The raw materials may include not only ingots, but also scrap generated during the manufacturing process, such as the production and pressing of aluminum alloy sheets. Furthermore, scrap from end-of-life vehicles (ELVs), such as car panels, wheels, radiators, and castings like engine blocks and suspensions, may also be used. Additionally, aluminum waste materials such as UBCs (Used Beverage Cans), home appliances, aluminum printing plates, electrical wires, and window frame scraps may also be used.
[0031] <Step 2: Homogenization Heat Treatment Process> Step 2 is a homogenization heat treatment process in which the ingot cast in Step 1 is subjected to a homogenization heat treatment. Homogenization heat treatment is a heat treatment performed to create a uniform structure throughout a cast material, as the structure and composition may be uneven in different areas after casting alone.
[0032] The homogenization heat treatment process is carried out at a temperature range of 520 to 580°C. After the homogenization heat treatment, the material is sent directly to the hot rough rolling process in step 3 without any cooling or additional heat treatment. This process is advantageous in terms of productivity because it does not involve cooling or additional heat treatment between the homogenization heat treatment process and the hot rough rolling process.
[0033] The temperature range of 520-580°C mentioned above refers to the start temperature of the homogenization heat treatment. Here, from the viewpoint of quickly homogenizing the structure, the temperature of the homogenization heat treatment is set to 520°C or higher, preferably 525°C or higher, and more preferably 530°C or higher. Furthermore, from the viewpoint of suppressing localized melting due to the lowered melting point of the segregated portion, the temperature is set to 580°C or lower, preferably 575°C or lower, and more preferably 570°C or lower.
[0034] In step 1 of this embodiment, the time for homogenization heat treatment is preferably 1 to 30 hours. Here, from the viewpoint of effectively eliminating segregation, the above time is preferably 1 hour or more, more preferably 2 hours or more, even more preferably 3 hours or more, and may be 4 hours or more. Also, from the viewpoint of productivity, the above time is preferably 30 hours or less, more preferably 20 hours or less, and even more preferably 10 hours or less.
[0035] <Process 3: Hot rough rolling process> Step 3 is a hot rough rolling process in which the ingot, which has been homogenized in Step 2, is hot rough rolled to obtain a hot rough rolled plate. Hot rough rolling is used to bring the homogenized ingot to the desired thickness. The hot rough rolling process is repeated using a reversible rolling mill until the desired thickness is reached.
[0036] The starting temperature for hot rough rolling, i.e., the entry temperature for the hot rough rolling process, is preferably 400 to 570°C. Here, it is preferable to achieve the desired thickness in as few reduction passes as possible during hot rough rolling. From the viewpoint of preventing an increase in the number of reduction passes due to high deformation resistance and difficulty in rolling, the above temperature is preferably 400°C or higher, and more preferably 500°C or higher. Furthermore, from the viewpoint of preventing the formation of coarse recrystallized grains on the surface, which can cause roughness in the final product, the above temperature is preferably 570°C or lower.
[0037] The final pass of hot rough rolling has a Z factor of 1.0 × 10⁻¹⁰, as shown in the following formula. 8 ~5.0×10 11 The procedure is carried out under the following conditions.
[0038]
number
[0039] (In the above equation, ε' represents the strain rate, Q represents the activation energy, R represents the gas constant, and T represents the temperature.)
[0040] To elucidate the recrystallization behavior during hot rolling in detail, the Zener-Hollomon parameter, known as the Z factor, which is a temperature-compensated strain rate, is used.
[0041] The larger the Z factor in the final pass of hot rough rolling, the more recrystallization is promoted during hot rough rolling and hot finish rolling, suppressing the formation of Mg-Si compounds due to processing strain. As a result, the amount of Mg-Si compounds remains low even after solution treatment. Furthermore, even if Mg-Si compounds precipitate during hot rough rolling, if the reduction ratio during hot rough rolling is large, i.e., the Z factor is large, the Mg-Si compounds become easily broken down into fine particles and are more likely to be dissolved after solution treatment. Therefore, the larger the Z factor in the final pass of hot rough rolling, the lower the number density of Mg-Si compounds after solution treatment, resulting in better bendability.
[0042] In addition to the above, when the Z-factor is large, the amount of accumulated strain increases, and uniform and fine recrystallized grains are formed after hot rough rolling. If uniform and fine recrystallized grains are obtained after hot rough rolling, uniform and fine recrystallized grains are likely to be formed even after any subsequent intermediate annealing or solution treatment, and surface roughening when the aluminum alloy sheet is press-formed can be suppressed.
[0043] That is, from the viewpoint of achieving good bendability by suppressing the formation of Mg-Si based compounds, and from the viewpoint of favorably suppressing surface roughening by forming uniform and fine recrystallized grains, the Z-factor of the final pass in hot rough rolling is set to 1.0×10 8 or more, preferably 5.0×10 8 or more, more preferably 1.0×10 9 or more. On the other hand, from the viewpoint of preventing rolling from becoming difficult due to rolling load constraints caused by an excessively low hot rough rolling temperature or an excessively large reduction in hot rough rolling, the above Z-factor is set to 5.0×10 11 or less, preferably 1.0×10 11 or less, more preferably 5.0×10 10 or less.
[0044] In the above formula for determining the Z-factor, ε' represents the strain rate, Q represents the activation energy, R represents the gas constant, and T represents the temperature, and ε' meaning the strain rate is determined by the following formula of Orowan & Pascoe.
[0045] [Formula]
[0046] In the above formula, v R represents the roll peripheral speed (mm / sec), R' represents the flattened roll radius (mm), h l represents the entry side sheet thickness (mm), and r represents the reduction ratio.
[0047] The thickness of the hot rough rolled sheet after the final pass is not particularly limited, and may be, for example, 10 to 100 mm.
[0048] <Step 4: Hot Finish Rolling Step> Step 4 is a hot finishing rolling process in which the hot rough-rolled sheet obtained in Step 3 is hot-finished to obtain a hot-finished rolled sheet. Hot finishing rolling is completed at a temperature of 250°C or higher and less than 350°C. Here, from the viewpoint of suppressing the decrease in productivity caused by the slowing of the finishing rolling speed due to coil cooling, the above completion temperature is 250°C or higher, and may also be 270°C or higher. Furthermore, from the viewpoint of reducing the number density of Mg-Si compounds and obtaining good bendability, the above completion temperature is less than 350°C, preferably less than 340°C, more preferably less than 330°C, and even more preferably 310°C or lower.
[0049] The thickness of the hot-finished rolled sheet finally obtained by step 4 is not particularly limited, but may be, for example, 3 to 10 mm.
[0050] The process may include an intermediate annealing step after the hot finishing rolling in step 4 and before the subsequent cold rolling step in step 5. In the case of aluminum alloy sheets, a texture is usually formed consisting of many orientation factors (crystal grains having each of these orientations), and crystal planes corresponding to these exist. Generally, the texture of rolled and recrystallized aluminum alloy sheets consists mainly of Cube orientation, Goss orientation, Brass orientation, S orientation, and Copper orientation. In the case of the texture of rolled sheet material, these textures are represented by the rolling plane and the rolling direction, with the rolling plane represented by {hkl} and the rolling direction by <uvw>It is expressed as follows. Based on this expression, each direction is expressed as follows. Cube direction {001} <100> Goss direction {011} <100> Brass direction (B direction) {011} <211> Cu orientation (Copper orientation) {112} <111> S direction {123} <634>
[0051] In contrast, hot-finished rolled sheets obtained by hot-finish rolling may not recrystallize. In such cases, intermediate annealing is preferable because it releases the strain in a state free from restraining forces, resulting in uniform and fine recrystallized grains and good surface quality. However, if the above recrystallization has occurred, intermediate annealing may not be necessary.
[0052] By performing recrystallization through intermediate annealing, followed by cold rolling with a cold rolling ratio of 74-95%, the area ratio of the cube orientation can be increased through recrystallization in the solution treatment in step 6, resulting in superior bendability.
[0053] The above intermediate annealing is preferably carried out in a temperature range of 300 to 450°C, and more preferably in a temperature range of 300 to 450°C for 1 to 20 hours. The temperature for the intermediate annealing described above is preferably 300°C or higher, more preferably 325°C or higher, and even more preferably 350°C or higher, from the viewpoint of obtaining good recrystallized grains. Furthermore, from the viewpoint of preventing the precipitation of Mg-Si compounds and the resulting decrease in flexibility, the temperature is preferably 450°C or lower, more preferably 425°C or lower, and even more preferably 400°C or lower.
[0054] The duration of the intermediate annealing described above is preferably 1 hour or more, more preferably 2 hours or more, and even more preferably 3 hours or more, from the viewpoint of bringing the coil to the desired annealing temperature and obtaining the effects of annealing favorably. Furthermore, from the viewpoint of preventing the Mg-Si compound from becoming coarse and reducing the bendability, the above duration is preferably 20 hours or less, more preferably 15 hours or less, and even more preferably 10 hours or less.
[0055] <Process 5: Cold Rolling Process> Step 5 is a cold rolling process in which the hot-finished rolled sheet obtained in Step 4 is cold-rolled to obtain a cold-rolled sheet. Cold rolling is a process that involves rolling an aluminum alloy sheet to a desired final thickness, either once or multiple times.
[0056] In step 5 of this embodiment, the cold rolling rate is set to 74-95%. Here, from the viewpoint of increasing the area ratio of the cube orientation after recrystallization in the subsequent solution treatment step 6 and achieving good bendability, the cold rolling rate is set to 74% or more, preferably 78% or more, and more preferably 80% or more. Furthermore, from the viewpoint of suitably controlling the area ratio of the cube orientation and maintaining good surface properties, the cold rolling rate is set to 95% or less, preferably 93% or less, and more preferably 91% or less.
[0057] If the cold rolling ratio is 74-95%, the thickness of the cold-rolled sheet is not particularly limited, but it may be, for example, 0.7-2.5 mm.
[0058] Furthermore, intermediate annealing may be performed during the cold rolling process. In this case, it is preferable to perform cold rolling with a cold rolling ratio of 74% or more after the intermediate annealing.
[0059] <Step 6: Solution Treatment Process> Step 6 is a solution treatment step in which the cold-rolled sheet obtained in Step 5 is subjected to solution treatment. Solution treatment is a process that involves solid-solving Mg and Si to ensure the yield strength after bakehard treatment.
[0060] The solution treatment is preferably carried out at a temperature of 520°C or higher, and more preferably in the temperature range of 520 to 580°C. Here, from the viewpoint of ensuring sufficient solid solution to achieve strength and suppressing the increase of Mg-Si compounds to achieve better bendability, the above temperature is preferably 520°C or higher, more preferably 525°C or higher, and even more preferably 530°C or higher. Furthermore, from the viewpoint of preventing eutectic melting and coarsening of recrystallized grains, the above temperature is preferably 580°C or lower, more preferably 575°C or lower, and even more preferably 570°C or lower.
[0061] The holding time for the solution treatment is not particularly limited, but for example, 1 to 300 seconds is preferred.
[0062] Cooling is performed after the solution treatment described above, with a cooling rate of 1 to 100°C / second being preferred. Here, from the viewpoint of suppressing the decrease in bendability due to grain boundary precipitation of coarse elemental Si phase and Mg-Si compounds, the cooling rate is preferably 1°C / second or higher, more preferably 5°C / second or higher, and even more preferably 10°C / second or higher. Furthermore, from the viewpoint of preventing a decrease in the flatness of the aluminum alloy sheet due to cooling strain, the cooling rate is preferably 100°C / second or lower, more preferably 80°C / second or lower, and even more preferably 60°C / second or lower.
[0063] The above cooling process cools the temperature to below 100°C, for example, to room temperature.
[0064] The method for manufacturing an aluminum alloy sheet according to this embodiment may further include a step of performing a pre-aging treatment after the solution treatment in step 6 and subsequent cooling. The preliminary aging treatment process involves cooling after the solution treatment, followed by a reheating treatment.
[0065] Preliminary aging treatment is preferably performed after the solution treatment step described above, that is, within 10 minutes after the solution treatment is completed and the material has cooled to room temperature, from the viewpoint of suppressing the decrease in bake hardness associated with the formation of Si-rich Mg-Si clusters due to room temperature aging.
[0066] The above preliminary aging treatment is preferably carried out in a temperature range of 50 to 100°C, and more preferably held in a temperature range of 50 to 100°C for 1 to 50 hours. Here, from the viewpoint of obtaining good bakehardness, the temperature of the preliminary aging treatment is preferably 50°C or higher, more preferably 55°C or higher, and even more preferably 60°C or higher. Furthermore, from the viewpoint of suppressing a decrease in bendability due to excessively high yield strength, the above temperature is preferably 100°C or lower, more preferably 95°C or lower, and even more preferably 90°C or lower.
[0067] From the viewpoint of obtaining good bakehardness, the duration of the above preliminary aging treatment is preferably 1 hour or more, more preferably 2 hours or more, and even more preferably 4 hours or more. Furthermore, from the viewpoint of preventing the yield strength from becoming too high and reducing the bending properties, the above duration is preferably 50 hours or less, more preferably 40 hours or less, and even more preferably 30 hours or less.
[0068] The above preliminary aging treatment is more preferably carried out within 10 minutes after the solution treatment process, by holding the temperature in the range of 50 to 100°C for 1 to 50 hours.
[0069] The steps for manufacturing the aluminum alloy sheet according to this embodiment have been described above, but other steps may be taken between or before / after each step, as long as they do not adversely affect the other steps.
[0070] <Aluminum alloy plate; composition> The aluminum alloy sheet obtained by the manufacturing method according to this embodiment satisfies the following alloy composition. Si: 0.3~1.5% by mass, Fe:0.15~0.4% by mass, Cu:0.001~0.2% by mass, Mn: 0.02~0.3% by mass, Mg: 0.3~0.8% by mass, Cr:0.001~0.3% by mass, Zn: 0.001~0.3 mass%, and Ti: satisfies 0.001~0.3 mass%, The remainder consists of Al and impurities.
[0071] Each component will be explained in turn.
[0072] ·Si:0.3~1.5% by mass Si is a major alloying element in aluminum alloy sheets and, along with Mg and Cu, contributes to improving the strength of aluminum alloy sheets. The Si content in aluminum alloy sheets is 0.3 to 1.5 mass%. Here, from the viewpoint of obtaining sufficient strength, the above content is 0.3 mass% or more, preferably 0.4 mass% or more, and more preferably 0.5 mass% or more. Furthermore, from the viewpoint of suppressing the formation of coarse elemental Si phases and Mg-Si compounds that reduce bendability, the above content is 1.5 mass% or less, preferably 1.25 mass% or less, and more preferably 1.0 mass% or less.
[0073] ·Fe:0.15~0.4% by mass Fe is an element that contributes to grain refinement through the particle-enhanced nucleation (PSN) mechanism. The Fe content in aluminum alloy sheets is 0.15 to 0.4 mass%. Here, from the viewpoint of suppressing deterioration of surface properties due to coarsening of recrystallized grains during intermediate annealing and other processes by generating a sufficient amount of Al-Fe compound that serves as a recrystallization nucleus through the particle-enhanced nucleation mechanism (PSN mechanism), the above content is 0.15 mass% or more, preferably 0.2 mass% or more, and more preferably 0.25 mass% or more. Furthermore, from the viewpoint of preventing a decrease in bendability due to an increase in Al-Fe compound, the above content is 0.4 mass% or less, preferably 0.35 mass% or less, and more preferably 0.3 mass% or less.
[0074] ·Cu:0.001~0.2% by mass Cu is an element that contributes to strength improvement through solid solution strengthening. The Cu content in aluminum alloy sheets is 0.001 to 0.2 mass%. Allowing the presence of Cu in aluminum alloys is economically advantageous because it enables the recycling of aluminum scrap containing Cu. However, corrosion resistance deteriorates as the Cu content increases. Therefore, from an economic standpoint, a Cu content of 0.001 mass% or more is preferable, and from the viewpoint of obtaining excellent intergranular corrosion resistance, the above content is 0.2 mass% or less, preferably 0.13 mass% or less, and more preferably 0.05 mass% or less.
[0075] ·Mn:0.02~0.3 mass% Mn is an element that contributes to grain refinement through the PSN mechanism. The Mn content in aluminum alloy sheets is 0.02 to 0.3 mass%. Here, from the viewpoint of obtaining good surface properties by refining the crystal grains through the formation of Al-Fe-Si-Mn compounds, the above content is 0.02 mass% or more, preferably 0.04 mass% or more, more preferably 0.05 mass% or more, and even more preferably 0.06 mass% or more. Furthermore, from the viewpoint of preventing a decrease in bendability due to an increase in Al-Fe-Si-Mn compounds, the above content is 0.3 mass% or less, preferably 0.25 mass% or less, and more preferably 0.2 mass% or less.
[0076] ·Mg:0.3~0.8% by mass Mg is a major alloying element in aluminum alloy sheets and, along with Si and Cu, contributes to improving the strength of aluminum alloy sheets. The Mg content in aluminum alloy sheets is 0.3 to 0.8 mass%. Here, from the viewpoint of obtaining sufficient strength, the above content is 0.3 mass% or more, preferably 0.35 mass% or more, and more preferably 0.4 mass% or more. Furthermore, from the viewpoint of suppressing the formation of coarse Mg-Si compounds that reduce bendability, the above content is 0.8 mass% or less, and from the viewpoint of good bendability and improved elongation, less than 0.75 mass% is more preferable, and even more preferably 0.70 mass% or less.
[0077] ·Cr:0.001~0.3 mass% Cr is an element that contributes to improved strength and ductility, as well as improved surface properties such as roughness, through grain refinement caused by compound formation. The Cr content in aluminum alloy sheets is 0.001 to 0.3 mass%. Allowing the presence of Cr in aluminum alloys is economically advantageous because it enables the recycling of aluminum scrap containing Cr. Therefore, from an economic standpoint, the Cr content is preferably 0.001 mass% or more, may be 0.002 mass% or more, or 0.004 mass% or more. Furthermore, from the viewpoint of suppressing the decrease in bendability due to the formation of coarse compounds, the Cr content is preferably 0.3 mass% or less, preferably 0.2 mass% or less, and more preferably 0.1 mass% or less.
[0078] ·Zn:0.001~0.3% by mass The Zn content in aluminum alloy sheets is 0.001 to 0.3 mass%. Allowing the presence of Zn in aluminum alloys is economically advantageous because it enables the recycling of aluminum scrap containing Zn. Therefore, from an economic standpoint, the Zn content is preferably 0.001 mass% or more, may be 0.002 mass% or more, or 0.004 mass% or more. On the other hand, from the viewpoint of suppressing a decrease in pitting potential and corrosion resistance, the Zn content is preferably 0.3 mass% or less, preferably 0.2 mass% or less, and more preferably 0.1 mass% or less.
[0079] ·Ti:0.001~0.3% by mass Ti is an element that is actively introduced as a microstructure refinement material by adding Al-Ti-B or Ti-B, and it is an element that contributes to microstructure refinement. The Ti content in aluminum alloy sheets is 0.001 to 0.3 mass%. Here, from the viewpoint of improving strength and ductility and improving surface properties such as roughness by microstructure refinement, the above content is 0.001 mass% or more, may be 0.002 mass% or more, or may be 0.004 mass% or more. Furthermore, from the viewpoint of suppressing the formation of coarse compounds that unfavorably affect the required properties, the above content is 0.3 mass% or less, preferably 0.2 mass% or less, and more preferably 0.1 mass% or less.
[0080] • Remainder: Al and impurities The basic components of the composition of the aluminum alloy plate in this embodiment are as described above, with the remainder being Al and impurities. Impurities are components other than those mentioned above, which may be present depending on the selection of raw materials for molten metal, including scrap from the ingot manufacturing process. However, their presence is permissible as long as it does not impair the various properties of the aluminum alloy sheet. Examples of impurities include V, B, Ni, Na, Pb, Be, Ca, Sn, In, Cd, Bi, and Ge.
[0081] Impurities include not only unavoidable impurities that are unintentionally and inevitably present, but also impurities that are intentionally added to the extent that they do not hinder the effects of the present invention. Unavoidable impurities are generally those that are inevitably mixed in when the raw materials are dissolved. As examples of impurities, the elements mentioned above may be included as unavoidable impurities, but they may also be added intentionally.
[0082] The content of each impurity component is preferably 0.05% by mass or less, and the total content of the impurity components is preferably 0.15% by mass or less.
[0083] As for the remainder of the aluminum alloy sheet, the Al purity, i.e., the Al content, is preferably 95% by mass or more, more preferably 96% by mass or more, and even more preferably 97% by mass or more.
[0084] <Aluminum alloy sheet; structure> The aluminum alloy plate obtained by the manufacturing method according to this embodiment preferably has an area ratio of 17 to 50% in the Cube orientation.
[0085] Here, the Cube orientation is known to be a crystal orientation advantageous for bendability, as described in Reference 1 below. On the other hand, the Cube orientation can also be a factor in the deterioration of surface properties, as described in Reference 2 below. (Reference 1: "Influence of Crystal Orientation on the Bendability of Al-Mg-Si Alloys," Hiroki Takeda et al., Light Metals, Vol. 60, No. 5, pp. 231-236 (2010)) Reference 2: "Crystal plasticity analysis of rising behavior occurring in Al-Mg-Si alloy sheets," Haruyuki Konishi et al., R&D Kobe Steel Techniques, Vol. 62, No. 2, pp. 39-42 (2012)
[0086] In contrast, from the viewpoint of achieving good bendability, the area ratio of the Cube orientation of the aluminum alloy in this embodiment is preferably 17% or more, more preferably 20% or more, even more preferably 21% or more, and even more preferably 25% or more. Furthermore, from the viewpoint of maintaining good surface properties, the area ratio is preferably 50% or less, more preferably 45% or less, and even more preferably 40% or less. As mentioned above, the above area ratio can be achieved through intermediate annealing, the cold rolling process in step 5, the solution treatment process in step 6, and so on.
[0087] In this embodiment, the area ratio of the Cube orientation of the aluminum alloy plate can be measured by the following method. A test specimen is cut from an aluminum alloy plate, embedded in polishing resin so that a cross-section parallel to the rolling direction can be observed, and the cross-section is polished to a mirror finish. Subsequently, ion etching is performed on the cross-section using X-ray photoelectron spectroscopy (ESCA; Electron Spectroscopy for Chemical Analysis), and the area ratio of the cube orientation is measured by irradiating the cross-section parallel to the rolling direction with an electron beam at a pitch of 5 μm in a range of "1.6 μm in the rolling direction × the thickness of the test specimen" using the electron backscattering diffraction (EBSD) method. Measurements using the EBSD method can be performed using, for example, a JEOL Ltd. FE-SEM7000F scanning electron microscope and a TSL Solutions Co., Ltd. photodetector, with the acceleration voltage of the measurement device set to 20kV. Here, the Cube orientation is defined as the {100} face being the surface of the plate, <001> For crystal grains whose orientation is parallel to the rolling direction, grains with an inclination angle of 15° or less from the ideal Cube orientation are defined as having a Cube orientation, and the area ratio of the Cube orientation is calculated.
[0088] The aluminum alloy plate obtained by the manufacturing method according to this embodiment has a number density of 2650 Mg-Si compounds with an equivalent circular diameter of 0.4 μm or more. 2 The following is preferable: The inventors have found a correlation between the number density of Mg-Si compounds with an equivalent circular diameter of 0.4 μm or more and their flexibility. In this specification, the term "Mg-Si compound" refers to an intermetallic compound containing Mg and Si as constituent elements.
[0089] As described above, from the viewpoint of achieving good bendability, the number density of Mg-Si compounds with an equivalent circular diameter of 0.4 μm or more is 2650 particles / mm². 2 The following is preferable: 2400 pieces / mm 2 The following is more preferable: 2250 pieces / mm 2 The following are even more preferable, and the fewer the better, for example, 1 piece / mm 2 That's fine too. The number density of Mg-Si compounds with an equivalent circle diameter of 0.4 μm or more can be achieved within the above range by factors such as the Z factor of the final pass in the hot rough rolling process of step 3 and the finishing temperature in the hot finish rolling process of step 3, as described above.
[0090] The number density of the above Mg-Si compounds can be determined by the following method. A test specimen is cut from an aluminum alloy sheet, embedded in polishing resin so that a cross-section parallel to the rolling direction can be observed, and then polished to a mirror finish. After that, gold is deposited on the cross-section to ensure conductivity, and then the area near the center of the sheet thickness is observed using a scanning electron microscope (FE-SEM). The FE-SEM instrument used is, for example, the JSM-7001F manufactured by JEOL Ltd., and observations are performed in COMPO mode at 1000x magnification with 50 fields of view, or 500x magnification with 20 fields of view. Based on the observations above, the black-colored particles are Mg-Si compounds, and the number density of those with an equivalent circular diameter of 0.4 μm or more will be calculated.
[0091] The aluminum alloy plate obtained by the manufacturing method according to this embodiment has an Al-Fe-Si compound number density of 225 to 700 particles / mm² with an equivalent circular diameter of 2.0 μm or more. 2 It is preferable that this be the case. Here, the term Al-Fe-Si compound as used herein refers to an intermetallic compound that contains Al and Fe as constituent elements and may also contain Si, Mn, Cr, etc.
[0092] As mentioned above, a high area ratio of cube orientation raises concerns about deterioration of surface properties. In contrast, from the viewpoint of achieving good surface properties through grain refinement, the number density of Al-Fe-Si compounds with an equivalent circle diameter of 2.0 μm or more is 225 particles / mm². 2 The above is preferable, with 300 pieces / mm 2 The above is more preferable, at 400 pieces / mm 2 The above is even more preferable. On the other hand, from the viewpoint of preventing an increase in Al-Fe-Si compounds that serve as crack initiation points and a decrease in bendability, the number density of Al-Fe-Si compounds with an equivalent circular diameter of 2.0 μm or more should be 700 particles / mm². 2 The following is preferable: 600 pieces / mm 2 The following is more preferable: 500 pieces / mm 2 The following are even more preferable. The number density of Al-Fe-Si compounds with an equivalent circle diameter of 2.0 μm or more can be achieved within the above range by adjusting the Fe and Mn content and the homogenization heat treatment conditions.
[0093] The number density of the above Al-Fe-Si compounds can be determined by observation using a scanning electron microscope (FE-SEM), similar to the number density of the Mg-Si compounds described above. Specifically, similar to the number density of the Mg-Si compounds described above, observations are made using, for example, a JSM-7001F manufactured by JEOL Ltd., at 1000x magnification with 50 fields of view, or 500x magnification with 20 fields of view, in COMPO mode. The Al-Fe-Si compounds appear white in the observation, and the number density is calculated for those with an equivalent circle diameter of 2.0 μm or more.
[0094] <Aluminum alloy sheet; properties> The aluminum alloy sheet obtained by the manufacturing method according to this embodiment achieves both excellent bendability and rhyming resistance.
[0095] The above-mentioned flexibility can be evaluated, for example, by a VDA bending test. The VDA bending test is a test conducted in accordance with the "VDA238-100 Plate bending test for metallic materials" standardized by the German Association of the Automotive Industry (VDA). The above test method will be explained using diagrams.
[0096] Figure 1 is a schematic perspective view of the apparatus used for the VDA bending test to evaluate bendability, the left side of Figure 2 is a front view of the apparatus, and the right side of Figure 2 is a side view of the apparatus. First, a plate-shaped test specimen obtained from an aluminum alloy sheet is placed horizontally and of equal length on two parallel rolls with a roll gap, as shown in Figure 1, as indicated by the dotted line in Figure 1. Specifically, the plate-shaped test specimen is placed horizontally and of equal length on the two rolls, such that its rolling direction and the direction of extension of a plate-shaped bending jig positioned vertically above it are perpendicular to each other, and its center is located in the center of the roll gap. Then, a bending jig is pressed from above against the center of the plate-shaped test piece to apply a load, and the plate-shaped test piece is bent (pushed bend) towards the narrow roll gap, pushing the center of the bent and deformed plate-shaped test piece into the aforementioned narrow roll gap. At this time, the bending angle (°) is measured at the point when the load F from the upper bending jig is at its maximum, that is, just before the bent tip of the central part of the plate-shaped test piece cracks. The magnitude of this bending angle serves as an indicator for evaluating the bendability.
[0097] The test conditions for the VDA bending test described above, as shown in Figure 1, are as follows: The plate-shaped test specimen is rectangular in shape with "width b: plate width after 10% stretch × length l: 60 mm", the diameter D of the two rolls is 30 mm each, and the roll gap L is (plate thickness of the plate-shaped test specimen × 2 + 0.5) mm. The depth of indentation of the center of the plate-shaped test specimen into the roll gap when the load F from the upper bending jig is at its maximum is S. The punch, which is a plate-shaped bending jig, has a tapered shape at the tip of the lower thin plate-shaped blade that presses against the center of the plate-shaped test specimen, with a radius r of 0.2 mm at the tip (lower end), as shown in Figure 2.
[0098] The plate-shaped test specimens to be used before the VDA bending test are prepared according to the following procedure. An aluminum alloy sheet is cut into strips measuring 250 mm in the direction parallel to rolling and 30 mm in the direction perpendicular to rolling. These strips are then subjected to aging treatment in an air furnace under conditions such as 90°C for 5 hours, 100°C for 5 hours, 110°C for 5 hours, and 120°C for 5 hours. Subsequently, a 10% stretch is performed in a tensile testing machine in the direction parallel to the rolling direction. A rectangular piece with a width b equal to the width and length l of the sheet after tensile stretching (10%) and a length l of 60 mm is then cut out to obtain a plate-shaped test specimen.
[0099] Using the plate-shaped test specimen described above, a VDA bending test is performed in accordance with the VDA238-100 standard described above, in which the bending line is perpendicular to the rolling direction. The speed at which the bending jig is pushed in until the load reaches 30N is 10mm / min, and the speed thereafter is 20mm / min. The bending process was set to stop when a crack occurred in the plate-shaped test specimen, or when the plate thickness of the test specimen decreased, resulting in a 30N reduction from the maximum load. The above bending test was performed twice for each aging treatment condition, and the bending angle (°) was the average value.
[0100] In the VDA bending test in this embodiment, the VDA bending angle at a yield strength of 150 MPa was determined. This yield strength was adopted based on the fact that, considering that the yield strength may increase and the bendability may deteriorate due to natural aging during hem bending at automobile manufacturers, the maximum yield strength that can be expected during hem bending is approximately 150 MPa.
[0101] The yield strength measured after 10% stretching is plotted on the x-axis and the VDA bending angle on the y-axis in a scatter plot. A linear approximation curve (y=ax+b) is obtained for each plot under each aging condition (e.g., 90°C × 5h, 100°C × 5h, 110°C × 5h, 120°C × 5h) using the least squares method, and y (VDA bending angle) is determined when x (yield strength) = 150.
[0102] Since the bending properties vary depending on the plate thickness, the VDA bending angle equivalent to a plate thickness of 1.0 mm is determined using the plate thickness conversion formula for the VDA bending angle described in the VDA standard. The above plate thickness conversion formula is as follows:
[0103]
number
[0104] In the above formula, α Soll This is the VDA bending angle equivalent value, and α ref is the VDA bending angle measurement, t is the plate thickness to be converted, and t ref This is the measured thickness of the plate.
[0105] Using the above formula, the VDA bending angle (converted to a plate thickness of 1.0 mm) equivalent to a yield strength of 150 MPa can be determined. If this value is 128° or higher, the bendability is considered good, 136° or higher is more preferable, 144° or higher is even preferable, and 150° or higher is even preferable.
[0106] The surface quality of the aluminum alloy sheet obtained by the manufacturing method according to this embodiment can be evaluated, for example, using a surface roughness index as a surface property.
[0107] The above skin irritation index is a value determined by the following method. First, to simulate the surface quality after press forming, the aluminum alloy sheet is subjected to strain by stretching using a tensile testing machine, and then its surface quality is evaluated. Common surface deterioration patterns observed in 6000 series alloys include rionic markings and roughness, but in this specification, roughness, which is a severe deterioration of properties beyond a predetermined range, is evaluated.
[0108] First, an aluminum alloy sheet is cut into a shape of "40 mm in the direction parallel to rolling × 200 mm in the direction perpendicular to rolling," and a tensile testing machine is used to stretch it by 10% in the direction perpendicular to the rolling direction to create a test specimen. Next, the degree of surface roughness of the test specimens is defined and evaluated, referring to the method described in Kobe Steel Technical Report / Vol.66 No.2 (Mar.2017). Specifically, a 3D surface roughness measuring instrument (Contour-GT, manufactured by Bruker Japan) is used to measure the surface shape of the above-mentioned test specimen in a 30mm x 30mm area. Then, after removing waveform components with wavelengths of less than 1mm or 5mm or more, the waveform components are classified according to their orientation relative to the rolling direction of the sheet material, and the sum of the amplitudes of each waveform component is calculated to quantitatively evaluate various surface defect forms that appear on the surface of the sheet material, such as roughness and rionic marks. Since roughness is the magnitude of irregularities that is independent of orientation, the degree of roughness can be expressed as a numerical index by summing the amplitudes of the waveform components in all directions and dividing by 360 (degrees).
[0109] In this specification, a surface texture is considered good if the skin roughness index is 52 μm or less, more preferably 48 μm or less, and even more preferably 42 μm or less.
[0110] The mechanical properties (strength) of the aluminum alloy sheet obtained by the manufacturing method according to this embodiment can be evaluated using the 0.2% yield strength determined by a tensile test.
[0111] The above-mentioned load-bearing capacity is a value determined by the following method. A 13A test specimen was taken from an aluminum alloy sheet, prepared in accordance with JIS Z 2201:1998, with the tensile direction perpendicular to the rolling direction, and a tensile test was performed at room temperature. The tensile test is performed at 5 mm / min until the 0.2% yield strength is measured, and then at 30 mm / min thereafter. If the yield strength after 3 to 14 days from obtaining the test specimen is between 80 MPa and 150 MPa, it can be said that the mechanical properties are good.
[0112] Furthermore, the mechanical properties of aluminum alloy sheets after baking paint are also important. Therefore, to simulate baked enamel coating, a 2% pre-strain was applied to the test specimen, followed by aging treatment (baked hard treatment) at 185°C for 20 minutes, and then a tensile test was performed. If the 0.2% yield strength after the bakehard treatment described above is between 190 MPa and 240 MPa, the mechanical properties can be considered good.
[0113] Aluminum alloy sheet The aluminum alloy plate according to this embodiment is an aluminum alloy plate obtained by the above-described "Method for Manufacturing an Aluminum Alloy Plate".
[0114] One embodiment of the aluminum alloy plate according to this embodiment satisfies the following alloy composition. Si: 0.3~1.5% by mass, Fe:0.15~0.4% by mass, Cu:0.001~0.2% by mass, Mn: 0.02~0.3% by mass, Mg: 0.3~0.8% by mass, Cr:0.001~0.3% by mass, Zn: 0.001~0.3 mass%, and Ti: satisfies 0.001~0.3 mass%, The remainder consists of Al and impurities.
[0115] In addition to the alloy composition described above, the number density of Mg-Si compounds with a cube orientation area ratio of 17-50% and an equivalent circle diameter of 0.4 μm or more is 2650 particles / mm². 2 The following conditions must be met, and the number density of Al-Fe-Si compounds with an equivalent circle diameter of 2.0 μm or more must be 225 to 700 particles / mm². 2 It is preferable that one or more of the following conditions regarding the organization be met, more preferably two or more, and even more preferably all three be met.
[0116] The descriptions and preferred embodiments regarding the alloy composition and microstructure described above are the same as those described in the "Method for Manufacturing Aluminum Alloy Sheets" above.
[0117] Furthermore, the aluminum alloy plate according to this embodiment has a VDA bending angle (calculated for a plate thickness of 1.0 mm) of 128° or more that corresponds to a yield strength of 150 MPa, and an average strength value A, which is an indicator of surface roughness. ave If both the value of and are 52 μm or less are met, it can be said that the aluminum alloy sheet has both excellent bendability and surface quality.
[0118] In addition to the above, it is preferable that at least one of the following characteristics be met: the yield strength after 3 to 14 days is 80 MPa or higher, and the 0.2% yield strength after bakehard treatment is 190 MPa or higher. It is more preferable that both conditions be met.
[0119] The descriptions of the above characteristics and preferred embodiments are the same as those described in the "Method for Manufacturing Aluminum Alloy Sheets" above. [Examples]
[0120] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples, and can be implemented with modifications to the extent that is consistent with its spirit, and all such modifications are included within the technical scope of the present invention.
[0121] [Example Test] <Example 1> The raw materials were melted, and the molten metal, whose composition was adjusted to match that of alloy A in Table 1, was cast into an ingot. The ingot was then surface-machined to remove the segregation layer on its surface. (Step 1) Next, the ingot underwent a one-step homogenization heat treatment, holding it at 560°C for 6 hours. (Step 2) After homogenization heat treatment, hot rough rolling was started immediately, with the entry temperature set to a range of 500-560°C, and the final pass had a Z factor of 7.63 × 10⁻⁶. 9 The procedure was carried out under the following conditions. (Step 3) Next, hot finishing rolling was performed. The finishing temperature for hot finishing rolling was set to 300°C, and the thickness of the hot-finished rolled sheet was set to 6.0 mm. (Step 4) Afterward, intermediate annealing was performed at 375°C for 4 hours. The hot-finished rolled sheet, which had undergone intermediate annealing, was cold-rolled. The resulting cold-rolled sheet had a thickness of 1.0 mm and a cold rolling ratio of 83%. (Step 5) Finally, a solution treatment was performed at 540°C, followed by cooling to room temperature at a cooling rate between 10 and 60°C / second. After approximately 5 minutes, the material was heated to 80°C and held for 4 to 30 hours to perform a preliminary aging treatment, thereby obtaining an aluminum alloy plate. (Step 6)
[0122] <Comparative Example 1> An aluminum alloy sheet was obtained in the same manner as in Example 1, except that the component composition was as shown in Alloy B in Table 1, and the conditions for hot finishing rolling, intermediate annealing, and cold rolling were changed to those described in Table 2.
[0123] <Comparative Example 2> An aluminum alloy sheet was obtained in the same manner as in Example 1, except that the conditions for hot finishing rolling were changed to those described in Table 2.
[0124] <Comparative Example 3> An aluminum alloy sheet was obtained in the same manner as in Example 1, except that the component composition was as shown in Alloy C in Table 1, and the cold rolling and solution treatment conditions were changed to those described in Table 2.
[0125] [Table 1]
[0126] [Table 2]
[0127] "evaluation" <Structure; Number density of Mg-Si and Al-Fe-Si compounds> A test specimen was cut from an aluminum alloy sheet, embedded in polishing resin so that a cross-section parallel to the rolling direction could be observed, and then polished to a mirror finish. After that, gold vapor deposition was performed on the cross-section to ensure conductivity, and then the area near the center of the sheet thickness was observed using a scanning electron microscope (FE-SEM). The FE-SEM (Field-Emission Scanning Electron Microscope) system used was the JSM-7001F manufactured by JEOL Ltd., and observations were performed in COMPO mode at 1000x magnification with 50 fields of view, or at 500x magnification with 20 fields of view. Based on the observations described above, the black-colored compounds were identified as Mg-Si compounds. Of these, the number density was calculated for those with an equivalent circle diameter of 0.4 μm or more, thereby determining the number density of Mg-Si compounds with an equivalent circle diameter of 0.4 μm or more. Furthermore, based on the results above, the white-looking compounds were identified as Al-Fe-Si compounds. Of these, the number density was calculated for those with an equivalent circle diameter of 2.0 μm or more, thereby determining the number density of Al-Fe-Si compounds with an equivalent circle diameter of 2.0 μm or more. The results are shown in Table 3.
[0128] <Organization; Area ratio of Cube orientation> Test specimens were cut from the obtained aluminum alloy plate, embedded in polishing resin so that a cross-section parallel to the rolling direction could be observed, and polished to a mirror finish. Subsequently, ion etching was performed on the cross-section using X-ray photoelectron spectroscopy (ESCA; Electron Spectroscopy for Chemical Analysis), and the area ratio of the cube orientation was measured by irradiating the cross-section parallel to the rolling direction with an electron beam at a pitch of 5 μm in a range of "1.6 μm in the rolling direction × the thickness of the test specimen" using electron backscattering diffraction (EBSD) method. Measurements using the EBSD method were performed using a JEOL Ltd. FE-SEM7000F scanning electron microscope and a TSL Solutions Co., Ltd. photodetector, with the acceleration voltage of the measurement device set to 20kV. Here, the Cube orientation is defined as the {100} face being the surface of the plate, <001> For crystal grains whose orientation is parallel to the rolling direction, grains with an inclination angle of within 15° from the ideal Cube orientation were defined as having a Cube orientation, and the area ratio of the Cube orientation was calculated. These results are shown in Table 3.
[0129] <Characteristics; Mechanical properties> From the obtained aluminum alloy sheet, a 13A test specimen was taken and prepared in accordance with JIS Z 2201:1998, with the tensile direction perpendicular to the rolling direction, and a tensile test was performed at room temperature. Tensile tests were performed at a rate of 5 mm / min until the 0.2% yield strength was measured, and then at 30 mm / min thereafter. The yield strengths mentioned above were determined after 4 days (Example 1, Comparative Example 1), 7 days (Comparative Example 2), or 8 days (Comparative Example 3) had elapsed since obtaining the test specimens. Furthermore, to assess the mechanical properties of aluminum alloy sheets after baking paint, tensile tests were also conducted on specimens that had been subjected to a 2% pre-strain followed by aging treatment (baked hardening) at 185°C for 20 minutes. These results are shown in Table 3.
[0130] <Evaluation; flexibility> The obtained aluminum alloy plates were subjected to VDA bending tests using the apparatus described above. Specifically, the plate-shaped test specimens to be used before the VDA bending test were prepared according to the following procedure. The obtained aluminum alloy sheet was cut into strips measuring 250 mm in the direction parallel to rolling and 30 mm in the direction perpendicular to rolling, and subjected to aging treatment in an air furnace at 90°C for 5 hours, 100°C for 5 hours, 110°C for 5 hours, and 120°C for 5 hours. Subsequently, it was stretched by 10% in the direction parallel to the rolling direction using a tensile testing machine, and a rectangular piece with width b being the width and length of the sheet after tensile stretching (10%) and length l being 60 mm was cut to obtain a plate-shaped test specimen. Using the plate-shaped test specimens described above, a VDA bending test was performed in accordance with the VDA238-100 standard, with the bending line perpendicular to the rolling direction. The speed at which the bending jig was pushed in until the load reached 30N was 10mm / min, and the speed thereafter was 20mm / min. The bending process was set to stop when a crack occurred in the plate-shaped test specimen, or when the plate thickness of the plate-shaped test specimen decreased, resulting in a 30N reduction from the maximum load. The bending angle θ after stopping was then measured. The above bending test was performed twice for each aging treatment condition, and the bending angle (deg.) was taken as the average value.
[0131] The 0.2% yield strength measured after 10% stretching was plotted on the x-axis and the VDA bending angle on the y-axis in a scatter plot. A linear approximation curve (y=ax+b) was obtained for each plot under each aging condition (90℃×5h, 100℃×5h, 110℃×5h, 120℃×5h) using the least squares method. Then, the y (VDA bending angle) when x (yield strength) = 150 (MPa) was calculated and converted to the case of a plate thickness of 1.0 mm to obtain the VDA bending angle equivalent to a yield strength of 150 MPa (converted to a plate thickness of 1.0 mm). The results are shown in Table 3.
[0132] <Evaluation; Surface Quality> The obtained aluminum alloy sheet was cut into a shape of "40 mm in the direction parallel to rolling × 200 mm in the direction perpendicular to rolling," and the sheet was stretched by 10% in the direction perpendicular to the rolling direction using a tensile testing machine to obtain the test specimen. Next, the power spectral intensity distribution in the frequency range of 1 to 5 mm was extracted from the two-dimensional power spectral intensity distribution of the two-dimensional surface roughness distribution. This was divided into multiple regions, and the absolute values of the power spectral intensity within each divided region were summed up to calculate the integrated intensity value. The average intensity value A was obtained by averaging the integrated intensity values for the multiple divided regions. ave This was used as an indicator value for skin irritation. Next, the three-dimensional surface roughness of the plate surface was measured, and after removing waveform components with wavelengths of less than 1 mm or 5 mm or more, the waveform components were classified according to their orientation relative to the rolling direction of the plate material, the sum of the amplitudes of each waveform component was calculated, and the amplitudes of the waveform components in all directions were summed and divided by 360 (degrees) to obtain a surface roughness index. The results are shown in Table 3.
[0133] [Table 3]
[0134] From the above results, it was found that this embodiment provides an aluminum alloy sheet that achieves both excellent bendability and surface quality.< / uvw>
Claims
1. Si: 0.3 to 1.5% by mass, Fe: 0.15 to 0.4% by mass, Cu: 0.001 to 0.2% by mass, Mn: 0.02 to 0.3% by mass, Mg: 0.3 to 0.8% by mass, Cr: 0.001 to 0.3% by mass, Zn: 0.001 to 0.3 mass%, and Ti: satisfies 0.001 to 0.3 mass%, The remainder is an aluminum alloy plate consisting of Al and impurities, The aforementioned aluminum alloy plate has an area ratio of 17-50% in the cube orientation. The number density of Mg-Si compounds with an equivalent circular diameter of 0.4 μm or more in the aforementioned aluminum alloy plate is 2650 particles / mm². 2 The following: The number density of Al-Fe-Si compounds with an equivalent circular diameter of 2.0 μm or more on the aforementioned aluminum alloy plate is 225 to 700 particles / mm². 2 It is an aluminum alloy plate.
2. An aluminum alloy sheet as described in claim 1, for use in automobiles.
3. The casting process involves melting raw materials and casting the molten metal, adjusted to a predetermined chemical composition, into an ingot. A homogenization heat treatment step in which the cast ingot is subjected to a homogenization heat treatment, A hot rough rolling process in which a homogenized ingot is hot rough rolled to obtain a hot rough rolled plate. A hot finishing rolling process to obtain a hot finishing rolled sheet by hot finishing rolling the aforementioned hot rough rolled sheet, A cold rolling process to obtain a cold-rolled sheet by cold-rolling the hot-finished rolled sheet, and A method for manufacturing an aluminum alloy sheet, comprising, in sequence, a solution treatment step of solution treatment of the cold-rolled sheet, The homogenization heat treatment step is performed in a temperature range of 520 to 580°C. Without performing cooling and additional heat treatment between the homogenization heat treatment step and the hot rough rolling step, The hot roughing process described above involves a final pass with a Z factor of 1.0 × 10, as shown by the following formula. 8 ~5.0 x 10 11 Perform the procedure under the following conditions: [Math 1] (In the above equation, ε' represents the strain rate, Q represents the activation energy, R represents the gas constant, and T represents the temperature.) The aforementioned hot finishing rolling process is completed at a temperature of 250°C or higher and less than 350°C. The cold rolling process is carried out so that the cold rolling ratio is 74 to 95%. The resulting aluminum alloy sheet is Si: 0.3 to 1.5% by mass, Fe: 0.15 to 0.4% by mass, Cu: 0.001 to 0.2% by mass, Mn: 0.02 to 0.3% by mass, Mg: 0.3 to 0.8% by mass, Cr: 0.001 to 0.3% by mass, Zn: 0.001 to 0.3 mass%, and Ti: satisfies 0.001 to 0.3 mass%, A method for manufacturing an aluminum alloy sheet, wherein the remainder consists of Al and impurities.
4. A method for manufacturing an aluminum alloy plate according to claim 3, wherein the homogenization heat treatment step is performed for 1 to 30 hours.
5. The method for manufacturing an aluminum alloy sheet according to claim 3 or 4, wherein the hot rough rolling step is performed with an entry temperature of 400 to 570°C.
6. A method for manufacturing an aluminum alloy sheet according to claim 3 or 4, comprising a step of performing intermediate annealing before or during the cold rolling step.
7. The method for manufacturing an aluminum alloy sheet according to claim 6, wherein the intermediate annealing is performed at a temperature range of 300 to 450°C for 1 to 20 hours.
8. The method for manufacturing an aluminum alloy plate according to claim 3 or 4, wherein the solution treatment step is performed in a temperature range of 520 to 580°C.
9. A method for manufacturing an aluminum alloy plate according to claim 3 or 4, wherein after the solution treatment, cooling is performed at a cooling rate of 1 to 100°C / second.
10. A method for manufacturing an aluminum alloy plate according to claim 3 or 4, wherein within 10 minutes after the solution treatment step, the plate is held at a temperature range of 50 to 100°C for 1 to 50 hours for a preliminary aging treatment.
Citation Information
Patent Citations
Method for producing aluminum alloy rolled material for forming having excellent bending workability and ridging resistance and composed of aluminum alloy
JP2018016879A